Davies, J.Q. 2014. Romantic Anatomies of Performance. Berkeley: University Of California Press. - Pierce, J. Mackenzie (Current Musicology, 2014)
What might a broken clavicle, a urinating Frédéric Chopin, the execution of parricides, and Sigismund Thalberg’s “third hand” all have in common? According to James Davies, these practices, accidents, and medical woes share nothing less than a concern for defining musical bodies. Romantic Anatomies of Performance offers a richly detailed history of hands, voices, and the music they made circa 1830. Travelling between London and Paris with the same alacrity as early nineteenth–century musicians, Davies marshals an impressive array of primary sources, including testimony by performers, composers, listeners, critics, and scientific researchers. By thickly describing the conflicts among participants in musical culture, Davies argues that music was itself as a site on which theories and practices of embodiment took shape. Davies’s scholarship contributes to several musicological sub–fields, most notably to the study of music and embodiment. Carolyn Abbate (2004) and Elisabeth Le Guin (2006) have trenchantly re–asserted the centrality of the body for musical experience. Moreover, they have shown how attention to performance’s materialities may generate musical knowledge of a type traditionally outside the purview of musicology. Davies is taking the next step in the study of music and body, as he brings a concern for embodiment to bear on nineteenth–century music in a new level of detail. Such a study is especially germane, as the musical practices cemented in the commercial centers of nineteenth–century Europe were arguably central to the formation of ideologies of modern art music more generally.